Journalism Education in Black and White: A 50-Year Journey Toward Diversity. (December 2020) - Wilkinson, Jeffrey S.; Davie, William R.; Taylor, Angeline J.
The struggle for equality in journalism education for African Americans raises questions about how the government, news media, and educators worked together to realize the principles of civil rights. Certain milestones over the past 50 years can be charted through the collective scholarship of this journal's pages. A careful look back reveals how goals of diversity were achieved or frustrated through reports on pedagogy, enrollment, technology, and trends in scholarship. Looking through the prism of Journalism & Mass Communication Educator ( JMCE ) offers a telling explanation of how journalism education moved away from segregation, and how the complicated relationship between predominantly White institutions (PWIs) and Historically Black Colleges and Universities (HBCUs) played a role in this journey.